Integration of Science and Islam in Geography Learning - Supini Supini; Sri Susanti Tjahja Dini (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The need for integration in learning is not only science but also includes Islamic values, this is very necessary to foster spiritual dryness, especially in science learning, and material demands when there is an integrated science competition. This requires educators to be able to create Islamic integrated learning in the Teaching and Learning Process. Sufficient references will help educators and students achieve learning objectives. This research uses R&D (Research and Development) research to produce products in the form of integrated geography supplement books with the Dick & Carry development model known as ADDIE. This research resulted in (1) the objectivity of the module but no Islamic integration was found in it (2) The product validity test resulted in scores from Material experts 82.7, Religious experts 84 and Design experts 88 with the achievement of a limited group test score of 84.7 very good categories and suitable for use. (3) There is an effectiveness of using the supplement book product for Geography teachers at MA level seen from the response during the limited trial on MGMP Geography teachers.